Seasonal influenza vaccines differentially activate and modulate toll-like receptor expression within the tumor microenvironment - Gupta, Kajal H.; Giurini, Eileena F.; Zloza, Andrew (Frontiers in Oncology, 2024)
Toll-like receptors (TLRs) are well-known for their role in cancer development as well as in directing anti-tumor immunityBecause TLRs have also been implicated in the innate recognition of the influenza virus, it was of great interest to investigate the potential TLR's contribution to the reduction in tumor growth following intratumoral injection of an unadjuvanted influenza vaccine and the lack of antitumor response from the adjuvanted vaccine. In our previous publication, we showed that the unadjuvanted flu vaccine modulates TLR7 expression leading to anti-tumor response in murine model of melanoma. Here, we show that the unadjuvanted and adjuvanted flu vaccines robustly stimulate different sets of TLRs, TLR3 and TLR7, and TLR4 and TLR9, respectively. In addition, the reduction in tumor growth and improved survival from intratumoral administration of the unadjuvanted vaccine was found to be diminished in TLR7-deficient mice. Finally, we observed that both vaccines have the capacity to modulate TLR expression on both innate and adaptive immune cells. Our findings add to the mechanistic understanding of the parameters that influence tumor outcomes in unadjuvanted and adjuvanted influenza vaccines.